Evaluasi atas Implementasi PP Nomor 23 Tahun 2018 dan Implikasinya Terhadap Penerimaan Pajak dan Kepatuhan Wajib Pajak UMKM di Banjarmasin - Agus Bandiyono; Nur Syifa Retno Utami (Journal of Applied Accounting and Taxation, 2021)
The aims of this study are to evaluate the implementation of PP No. 23 of 2018 at KPP Pratama Banjarmasin Utara and Selatan, to analyze the implications of the implementation of PP No. 23 of 2018 on tax revenue and compliance of SME taxpayers, and to find out the challenges and obstacles in implementing regulations at KPP Pratama Banjarmasin Utara and Selatan. The research method used are the qualitative method of library research and field research in the form of interviews and observations. The results of the research are based on observation, interviewing informants and evaluating the implementing regulations, PP No. 23 of 2018 has been implemented properly. PP No. 23 of 2018 has a positive effect on the revenue and number of SME taxpayers who make tax payments, but it has not made a positive contribution to the compliance of SME taxpayers in reporting annual tax return. This is known through the percentage of SME taxpayers’s annual tax return reporting compared to the number of SME taxpayers registered in Banjarmasin less than 20%. The challenge in implementing this PP is in providing education and awareness of taxpayers who are still low. The perceived obstacles are that taxpayers are not familiar with technology, dependence of taxpayers on officers, and double taxation.